Spatiotemporal variation and exposure risk to human health of potential toxic elements in suburban vegetable soils of a megacity, SW China, 2012–2016 - Bing, Haijian; Xiang, Zhongxiang; Zhu, He; Wu, Yanhong (Environmental science and pollution research international, 2018)
Trace element contamination in soils of vegetable fields can threat public health. Seven potential toxic elements (As, Cd, Cr, Cu, Ni, Pb, and Zn) in suburban vegetable soils of Chengdu city, Southwest China, in 2012 and 2016, were analyzed to identify their sources with the spatiotemporal variation and assess their contamination and health risk for residents. The results showed that the concentrations of soil elements did not increase significantly in 2016 compared with that in 2012, whereas their spatial distributions altered markedly. The hot spots of soil As, Cd, and Pb as well as Cu and Zn in 2016 revealed the anthropogenic sources including agricultural activities, industrial emissions, road dust with heavy traffic, and open burning of solid waste. The apparent spatial difference of anthropogenic elements was related to the layout of land use surrounding the vegetable field. The contamination of soil elements decreased in the order of Cd > As ≈ Zn > Cu ≈ Pb > Cr ≈ Ni in 2012 and Cd > Zn > As ≈ Cu ≈ Pb > Cr ≈ Ni in 2016, and the vegetable soils were slightly to moderately contaminated by these elements through integrated contamination index. The sites affected by the trace elements did not increase in 2016 than in 2012, whereas the sites with relatively high contamination increased markedly. The non-carcinogenic risk of trace elements was generally acceptable, and children showed higher health risk than adults. The As carcinogenic risk for children varied between 5.48 × 10 −5 and 1.59 × 10 −4 in 2012 and between 4.40 × 10 −5 and 1.82 × 10 −4 in 2016, and the sites above acceptable levels (> 10 −4 ) reached 60.6% and 48.5% in 2012 and 2016, respectively. The health risk of As in the vegetable soils should be paid more attention due to its high toxicity.